Replacing the use of live mussels with artificial mussels to monitor and assess the risks of heavy metals. Issue 1 (2nd January 2023) - Kibria, Golam; Stark, Robert; Nugegoda, Dayanthi; Wu, Rudolf
ABSTRACT: In the last few decades, biomonitors especially live mussels (LM) have been commonly used to monitor heavy metals in aquatic systems worldwide. This study examined the feasibility of replacing the use of live biomonitors with artificial mussels (AM) in monitoring heavy metals. Laboratory experiments were conducted to compare metal accumulation in the freshwater mussel, Velesunio ambiguus (live mussels or LM) with that of AM exposed to varying concentrations of copper, lead and zinc over a 28-day period. Furthermore, field studies were carried out to compare metal accumulation in V. ambiguous at three sites with a range of different levels of metal contamination in regional Victorian waterways, Australia. Our results showed that LM showed preferential uptake of metal, whereas AM showed no preference in the accumulation of heavy metals. Artificial mussels are a reliable tool for assessing risks posed by heavy metals in waterways (fresh, brackish or marine) since the accumulation of heavy metals in AM is not affected by biotic and abiotic factors. We concluded that AM can be an effective and excellent replacement for live biomonitors such as native mussels in monitoring heavy metals in freshwater systems.